Polyglossia and Nativization. The translation of zoonyms in early Dutch Bibles. Research material. - de Smit, Merlijn (Stockholm University, 2021)
This study deals with the translation of exotic zoonyms in early Dutch Bibles. By looking at which course of action a translator has taken (for example, translating a zoonym as exactly as possible, or using a more familiar Dutch zoonym instead) I want to discern the ideology underlying a translation (for example, loyalty towards a tradition of source texts or maximal adaptation to a standard language). Data consists of the translation equivalents of thirty zoonyms in the Old Testament sections (minus the psalms) of five Dutch translations from 1477 to 1548. Also, source languages in Hebrew, Greek and Latin were examined, as was Luther's Bible translation of 1534.

Data has been selected through reading relevant sections of the Old Testament.

Studien handlar om översättning av exotiska djurnamn i tidiga nederländska Bibelöversättningar. Genom att titta på hur en översättare har löst ett problem (till exempel, att översätta ett exotisk djurnamn så exakt som möjligt eller alternativt använda ett mindre exakt men mer vanlig nederländsk djurnamn istället) vill jag studera vilka ideologier en översättning bygger på (t.ex. lojalitet gentemot en textuell tradition eller maximal anpassning till målspråket). Forskningsdata är översättningsekvivalenter av trettio djurnamn i Gamla Testamentet (minus psalmerna) i fem nederländska bibelöversättningar från 1477 till 1548. Källtexter i grekiska, latinska och hebreiska har också tagits i beaktande, liksom Luthers översättning från 1534.

Data har insamlats genom läsning av relevanta sektioner av Gamla Testamentet,
Polyglossia and Nativization. The translation of zoonyms in early Dutch Bibles. Research material.
Keywords: translation; översättning; Bible; Bibeln; lutheranism; lutherdom; reformation; reformation; onomastics; onomatologi; Studies of Specific Languages; Studier av enskilda språk; Studies of Specific Literatures; Litteraturstudier